Different pitch configurations constrain the external and internal loads of young professional soccer players during transition games - Asian-Clemente, Jose A.; Rabano-Muñoz, Alberto; Suarez-Arrones, Luis; Requena, Bernardo (Biology of Sport, 2023)
The aims of this study were to compare the influence of transition game (TG) size on the external and internal loads of young professional soccer players and to describe the high speed profile of these drills in response to pitch dimensions. Eighteen young professional soccer players (age: 16.1 ± 0.3 years; height: 178.3±5.4 cm; weight: 70.1±6.2 kg) performed a 3vs2 TG on pitches measuring 40×30 m (TG 30 ), 40×50 m (TG 50 ) and 40×70 m (TG 70 ) m. Distance covered (DC); accelerations-decelerations above 1.0 m·s −2 and 2.5 m·s −2 ; rate of perceived exertion (RPE); maximal heart rate and time above 90%; DC at 18.0 to 21.0 km · h −1 (DC 18–20.9 km · h −1 ); DC at 21.0 to 23.9 km · h −1 (DC 21–23.9 km · h −1 ); DC above 24.0 km · h −1 (DC > 24 km· h −1 ); and peak speed and sprint profile (duration, distance and maximal speed) were measured. TG 30 achieved lower DC, DC above 18 km·h −1 , peak speed, sprint distance and RPE than TG 50 and TG 70 (p < 0.01 and p < 0.05) and lower sprint duration and maximal speed sprint than TG (p < 0.01). TG 30 and TG 50 achieved higher Acc > 1.0 and > 2.5 m·s −2 respectively than TG 70 (p < 0.05). TG 70 showed greater DC above 21 km·h −1 , peak speed, sprint distance and maximal speed sprint than TG 50 (p < 0.01). Soccer coaches should use larger TGs to overload variables related to high speed and sprint demands during training and smaller TG formats to stimulate the accelerations of the soccer players.